Julián Ríos and the book-world (1994) - Hatoum, Milton (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This interview was published in the diary Folha de S. Paulo newspaper on March 13, 1994.
Keywords: Julián Ríos; Milton Hatoum